Subjek dan Objek Pajak Penghasilan - Annisa Febrianda; Rania Atikah Putri; Siti Nurhaliza; Dini Vientiany (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Basically, income tax itself is an official levy aimed at people who earn income or for the income they receive or obtain from the tax year for the benefit of the state and the interests of society in national and state life as an obligation that must be carried out. In this research, the method used is a literary research method, including the type of library research. Income tax (PPh) is a tax imposed on the income of individuals, companies or other legal entities on income received or earned during the tax year.